Every day is Earth Day [videorecording (DVD)] (PBS Kids, 2025)
Kids can learn to care for and celebrate the Earth and all its wonders with fun PBS Kids stories. Arthur helps Prunella prepare for the school₂s Earth Day fair. When the Fuzzytown Park gets covered in garbage, Carl learns that trash is a collection you don't keep. Daniel Tiger's class goes on a nature walk. Molly and Tooey count endangered beluga whales. Nature Cat and friends take an Earth Day nature hike and clean up litter along the way. Chris and Martin learn how nature works in harmony. And much more!